Relationship Between Swim Start Wall Contact Time and Final Performance in Backstroke Events in International Swimming Championships - Garcia-Hermoso, A (Routledge, 2017)
The purpose of this study was to investigate the association between race-start wall contact time and final performance for each sex as a function of classification and anti-slip start-device use (with or without) in backstroke events of international competitions. Twenty-one international competitions covering a 10-year period (2006-2015) were analysed, retrospectively. The data corresponded to the competition histories of 1723 swimmers. For the contact-time data of each event (50-m, 100-m and 200-m), two-way ANOVAs (sex × classification and sex × start device use) were performed. The Bonferroni post-hoc test was used to compare means, and Pearson’s simple correlation coefficient to determine possible correlations between wall contact times and final performance. The results showed the men to have shorter wall contact times than the women in the 50-m and 100-m events, and that, for the women medallists, their wall contact times were positively correlated with final performance in all events except the 200-m swim without the start device. © 2017 Cardiff Metropolitan University.